Pengaruh Struktur Modal, Likuiditas, Dan Leverage Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Subsektor Industri Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2020) - Lutfi Amalia Masfiro; Muhammad Agus Salim; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to determine the effect of capital structure, liquidity, and leverage on firm value in manufacturing companies in the food and beverage industry sub-sector listed on the Indonesia Stock Exchange in 2017-2020. The sample used in this study were 14 companies using a sampling technique, namely purposive sampling. The data analysis technique used is multiple linear regression analysis using the Eviews10 application as a tool. The results of this study indicate that capital structure has a negative effect on firm value, liquidity has a negative effect on firm value, and leverage has a positive effect on firm value. Keywords : Capital Structure, Firm Value, Leverage, Liquidity